Solving Sprawl: Models Of Smart Growth In Communities Across America - F. Kaid Benfeild (Island Press, 2003)
The book details 35 diverse smart-growth stories from around the United States and celebrates those who are leading the way in solving sprawl - and local officials who have embraced new forms of development, corporations who are choosing to redevelop abandoned city properties rather than build new corporate campuses on undeveloped land, faith-based organizations that have been instrumental in redeveloping inner-city neighborhoods, visionary architects and planners who are showing how to design communities and regions that solve sprawl. Each chapter showcases a wide variety of solutions with projects of all sizes in urban, suburban, and exurban settings including Adidas Village in Portland, Oregon; the MCI Center in Washington, D.C.; Quality Hill in Kansas City, Kansas; Suisun City redevelopment in Suisun City, California; growth control initiatives in Boulder, Colorado; Pearl Lake in Almira Township, Michigan; and more. Interspersed throughout are sidebars that offer additional examples and reminders of the sprawl-related environmental and social problems that smart growth helps overcome. The book also includes a glossary of planning terms and land-use concepts.